2015
DOI: 10.7759/cureus.351
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Lateral Lumbar Interbody Fusion (OLLIF): Technical Notes and Early Results of a Single Surgeon Comparative Study

Abstract: Background context: Lower back pain is one of the most prevalent and expensive health conditions in the Western world. The standard treatment, interbody fusion, is an invasive procedure that requires the stripping of muscles and soft tissue, leading to surgical morbidity. Current minimally invasive (MI) spinal fusions are technically demanding and suffer from technical limitations.Purpose: Oblique lumbar lateral interbody fusion (OLLIF) is a new technique for fusion of the lumbar spine that overcomes these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…Both of these obstacles have been overcome with the OLLIF technique. We have previously demonstrated that OLLIF is not technically challenging and produces superior results compared to open surgeries [15]. The present study demonstrates that these outcomes are transferable to a group of patients with deformity.…”
Section: Discussionsupporting
confidence: 66%
“…Both of these obstacles have been overcome with the OLLIF technique. We have previously demonstrated that OLLIF is not technically challenging and produces superior results compared to open surgeries [15]. The present study demonstrates that these outcomes are transferable to a group of patients with deformity.…”
Section: Discussionsupporting
confidence: 66%
“…LIF via Kambin's triangle is a type of MIS-TLIF, which is a microendoscopy-assisted surgery that uses a small incision. Recently, a less invasive percutaneous LIF technique via Kambin's triangle has also been reported [18][19][20] . Various reports characteristically state how exiting nerve root injury can be avoided during cage insertion.…”
Section: Discussionmentioning
confidence: 99%
“…By fully covering the cranial side of the cage by this J-shaped retractor, we were able to reduce the risk of having the cage in direct contact with the exiting nerve root. Abbasi et al 20) in their study inserted a guidewire in the middle of the disk from Kambin's triangle and prepared the graft site and inserted the cage via that guidewire. To avoid damage to the exiting nerve root, they used a cage that was shaped to facilitate its avoidance to the exiting nerve root.…”
Section: Discussionmentioning
confidence: 99%
“…The operating room (OR) times for this procedure are lower than any previously reported OR times for fusions of the thoracic spine [17, 21]. No patient stayed in the hospital for more than three days and there were no complications apart from one clinically insignificant case of hemothorax.…”
Section: Discussionmentioning
confidence: 86%